(untitled) (The Review of Diabetic Studies, 2024)
Primary Health Care (PHC) stands as the cornerstone of equitable, efficient, and resilient health systems, with General and Family Medicine (FM) serving as its indispensable clinical engine. This research paper employs a comprehensive conceptual analysis, supported by a review of international case studies and evidence, to argue that FM is the critical discipline for strengthening PHC and implementing effective disease prevention. The analysis explores the profound alignment between the philosophy of FM—characterized by first-contact accessibility, longitudinal continuity, comprehensiveness, and coordination—and the core principles of the PHC model. It further elucidates the dual role of family physicians as gatekeepers, optimizing system efficiency, and navigators, ensuring integrated care for individuals with multimorbidity and mental health needs. The paper details the implementation of the prevention triad (primary, secondary, tertiary) within the context of continuous, person-centered care. Despite its proven value, significant barriers are identified, including workforce shortages, misaligned financing models, and systemic constraints that favor hospital-centric care. Examination of successful international case studies reveals that strategic investment in FM education, blended financing, interprofessional teams, and digital health infrastructure yields superior health outcomes and sustainability. The paper concludes that the path to stronger health systems globally necessitates a paradigm shift: from rhetoric to decisive policy and investment in Family Medicine as the foundational pillar for achieving health for all.